Deutschland Einwanderungsland. Begriffe - Fakten - Kontroversen. 3., überarb. u. erw. Aufl. - (:unkn) unknown (Kohlhammer, 2017)
Die Themen Migration und Integration haben sich zu einem eigenständigen Politikfeld entwickelt. Politik und Wirtschaft, Öffentlichkeit und Medien sind sich einig, dass es sich um zentrale Themen der Zukunft handelt. Migration und Integration sind aber nicht nur in aller Munde, sondern auch praktisches Politikfeld, auf dem sich Zehntausende professionell oder ehrenamtlich engagieren.

The issues of migration and integration have dynamically evolved in recent years to become stand-alone policy areas. Politics and business, the public and the media are in agreement that these are key issues for the future. The issues of migration and integration are not only on everyone?s lips, but are increasingly becoming a practical policy area at all levels of administration, where tens of thousands of people are dealing with these issues, both professionally and voluntarily. The publishers of this book have compiled a handy compendium, which offers reliable information on over 60 key terms from the policy area of migration and integration in the form of short, factual articles from well-known authors from all over Germany.
Keywords: Bevölkerungsentwicklung; Ausländer; Einwanderung; Integration; Gesellschaftsordnung; Konfession; Institution; Wirtschaft; Politik; Migrant; Staatsangehörigkeit; Flüchtlingsrecht; Asylrecht; Sozialengagement